Pengaruh Pengalaman Kerja Terhadap Produktivitas Pegawai Kerja Di Kantor Sekretariat Daerah Kabupaten Gowa - Hidaya, Nur; Burhanuddin, Burhanuddin; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2020)
This study purposed to determine the effect of work experience on work productivity in the Regional Secretariat Office of Gowa Regency. The research method was a quantitative research method with the type of survey research. The hypothesis put forward work experience on work productivity. Data obtained by 114 respondents, while the sample used a creative table which was followed by stratified random sampling. Data analysis technique used a simple linear regression analysis method with Y = 10.978 + 0.683X with the help of Pearson product moment (r) through SPSS Version 22.0 program at α = 0.05 level. The results of this study showed that there was a significant positive influence between work experience on work productivity in the Regional Office of the Gowa Regency Secretariat with a regression coefficient of 0.683 for the interpretation of the regression cofficient in the medium category so that it could be said that there was an effect of work experience on work productivity in the Gowa Regency Regional Secretariat Office.